Kecerdasan Intelektual, Kecerdasan Spiritual, dan Kecerdasan Finansial Terhadap Pemahaman Akuntansi Mahasiswa di Universitas Sarjanawiyata Tamansiswa - Erawati, Teguh; Kasih, Dwicky Putra; Listyawati, Reni (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to prove the influence of intellectual intelligence, spiritual intelligence and financial intelligence on the understanding of accounting students at Sarjanawiyata Tamansiswa University. the theory of planned behavior is used to test the relationship between each variable, namely the independent and dependent variables. The method used in this research is a quantitative research method. The number of respondents used in this study were 155 respondents who were taken using the purposive sampling technique for accounting students at Sarjanawiyata Tamansiswa University. The test used in the study is the validity test, the reliability test is used for the feasibility questionnaire. Data analysis techniques used in this study are descriptive statistical tests, classical assumption tests and hypothesis test. The results of this study indicate that intellectual intelligence, spiritual intelligence and financial intelligence have a positive and significant effect on understanding accounting. This research contributes to providing a reference for increasing students' understanding of accounting through the levels of intellectual intelligence, spiritual intelligence and financial intelligence.